The Role of Erythrocyte Membrane Proteins in Haemolytic Anaemias in South African Populations - Vallet, Lara Dominique (My University, 2006)
The erythrocyte carries gases between the cells and the lungs, and has to distort to negotiate narrow splenic sinuses and capillaries. This distortion necessitates a high surface area to volume ratio that is maintained by the erythrocyte membrane skeleton, a network of proteins including spectrin and protein 4.1. The skeleton anchors the lipid bilayer through attachment to integral membrane proteins, notably the anion exchange protein, band 3. Abnormalities of the erythrocyte membrane proteins cause loss of cell elasticity and ultimately the erythrocytes become prematurely trapped in the spleen where they are phagocytosed, resulting in haemolytic anaemia. Three mutations causing band 3-deficient hereditary spherocytosis (HS), a haemolytic anaemia characterised by spherical erythrocytes, were located using restriction enzyme analysis and DNA sequencing. Proband A (Black) is heterozygous for band 3 Pinhal (R490H) and has mild clinical symptoms. Proband B and his mother (Caucasian) are heterozygous for band 3 Bicetre (R490C) and have severe anaemia requiring transfusions and splenectomy, respectively. These results confirm codon 490 as a hotspot for mutations and indicate the effect of different amino acid substitutions in the same position on clinical severity. Proband C (Black) is homozygous for a novel mutation (E508K) for which her parents are heterozygous. The proband is severely affected and transfusion- dependent whereas her father has moderate anaemia and her mother is asymptomatic. It is speculated that a secondary factor modulates their clinical symptoms. All of these mutations occur in a CpG dinucleotide, a common source of DNA mutations, and are located within the highly conserved exon 13, which encodes the third to fifth α-helices and the second extracellular loop of the transmembrane region of band 3. The mutations are likely to alter the conformation of band 3, impairing its insertion into the erythrocyte membrane. No causative mutations were located in another 12 band 3-deficient HS kindred using restriction enzymes and single strand conformation polymorphism analysis. Ten protein 4.1-deficient patients with hereditary elliptocytosis, a haemolytic anaemia characterised by elliptical erythrocytes, were also studied. Immunoblot analyses ruled out abnormally sized protein 4.1 and three known DNA mutations were excluded using restriction enzyme analysis. Further studies are required to elucidate the cause of the haemolytic anaemia in these kindred. This study advanced our knowledge of the molecular basis of HS in South African kindred and highlighted the susceptibility of CpG dinucleotides to mutations.
Faculty of Science School of Pathology(Molecular Medicine and Haematology). 9707563v tridium@acenet.co.za
Keywords: Haemolytic Anaemia; Herediatary Elliptocytosis; Erythrocyte band 3; Anion Exchange Protein 1; Erythrocyte Protein 4.1